2024
DOI: 10.1101/2024.03.07.583875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A history of repeated antibiotic usage leads to microbiota-dependent mucus defects

Kertu Liis Krigul,
Rachel H. Feeney,
Supapit Wongkuna
et al.

Abstract: Recent evidence indicates that repeated antibiotic usage lowers microbial diversity and lastingly changes the gut microbiota community. However, the physiological effects of repeated - but not recent - antibiotic usage on microbiota-mediated mucosal barrier function are largely unknown. By selecting human individuals from the deeply-phenotyped Estonian Microbiome Cohort (EstMB) we here utilised human-to-mouse faecal microbiota transplantation to explore long-term impacts of repeated antibiotic use on intestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…But rather, that a direct effect on the host also exists. Indeed, a recent study has shown that transferring microbiota from humans with a history of antibiotic use to mice can cause mucus barrier defects in mice 30 .…”
Section: Discussionmentioning
confidence: 99%
“…But rather, that a direct effect on the host also exists. Indeed, a recent study has shown that transferring microbiota from humans with a history of antibiotic use to mice can cause mucus barrier defects in mice 30 .…”
Section: Discussionmentioning
confidence: 99%